Frog and toad together - Lobel, Arnold ([New York] : HarperCollins Publishers, 1972)
Five further adventures of two best friends as they share cookies, plant a garden, and test their bravery.
"A Newberry honor book"--Cover.
Keywords: Frogs -- Juvenile fiction; Toads -- Juvenile fiction; Animal fiction